Marketing Strategies For Tilapia Aquaculture: A Case Study of Chery Caramon In Sukamaju Village, Abung Tinggi District, North Lampung Regency - Amanda, Haifa; Purnomo, Agus (Indonesian Journal Publisher, 2025)
Tilapia has become one of the most popular and widely consumed fish by the community. Tilapia has become one of the commodities for people in Indonesia, one of which is located in North Lampung. Chery Caramon is the only tilapia producer that focuses on tilapia cultivation as one of the commodities to drive the local economy. This study focuses on knowing the marketing strategy of Chery Caramon's tilapia farming business in Abung Tinggi District, North Lampung Regency. This study uses a descriptive method with a case study approach to find out the marketing strategies used by Chery Caramon. This study uses SWOT analysis to find out various opportunities and threats that are factors for Chery Caramon to improve its tilapia farming marketing strategy. From this research, it can be concluded that tilapia farming by Chery Caramon in North Lampung Regency uses an SO (Strength-Opportunity) strategy to market its products to the surrounding community.